Australia: Corruption Scandal and International Students - Welch, Anthony (International Higher Education, 2024)
Australia’s considerable success in attracting substantial numbers of international students has come at a cost. A USD 27 billion industry has grown up, and it is inadequately regulated. Loopholes in the visa system allow corrupt agents to organise a student visa to a reputable university, while simultaneously planning to switch the student to a lower-quality training provider, who offers a higher commission. More regulation of education agents is urgently needed.